Book Review: Theoretical and applied perspective on teaching foreign languages in multilingual settings: Pedagogical implications - Shahzad- (Journal of Pedagogical Research, 2024)
Inclusivity is an idea much cherished in the modern theory of multilingualism and encouraged in its pedagogical practices. Language teaching is no longer an isolated endeavor in a static monolinguistic classroom environment, rather it involves adopting a holistic approach towards linguistic capabilities and cultural identities, using them to establish a congenial teacher-learner relationship. Along these lines, Theoretical and Applied Perspective on Teaching Foreign Languages in Multilingual Settings: Pedagogical Implications is a timely work that presents a comprehensive introduction to the research in the emerging field of multilingual practices in foreign language (FL) learning and teaching. It addresses the question of how to foster an inclusive environment for the acquisition/teaching of a foreign language by utilizing learners' heritage and sociolinguistic resources. It also connects the research with viable linguistic/instructional practices in order to strengthen the teaching-learning process in multicultural and multilingual globalized classrooms. The volume is composed by a plethora of writers from varying linguistic, social, and racial backgrounds and edited by Anna Krulatz, Georgios Neokleous and Anne Dahl. The edited book encompasses theoretical, methodological, and empirical perspectives on the multilingual turn in foreign language education and is the outcome of over three years of collaborative work across the continents of Europe, Asia and North America. In every chapter, the authors explore theoretical and pedagogical implications across different contexts and spaces, delving into the challenges and opportunities facing teachers and learners in the process of promoting multilingualism. Expressing an appreciation of students' diverse linguistic abilities and acknowledging the effective role of multilingualism, this collection aims to credit teachers' agency to allow a rhetoric of differences while resisting the dominant monolingual ideology. Language education, which has been predominantly influenced by monolingual bias in the past, is now undergoing a paradigm shift towards multilingualism and translanguaging practices that value learners' multicompetencies and repertoires (Conteh & Meier, 2014; May, 2019). Broadly, the authors present a comprehensive report of their findings in practical research on topics such as the role of translanguaging in the foreign language classroom, the role of learners' own languages in learning new languages, appreciation of cultural and linguistic diversity in inclusive foreign language pedagogies, and teachers' and learners' attitudinal approach to multilingualism. The book can be beneficial for all international institutions-linguistically diverse campuses hosting students from varying social and linguistic backgrounds. As the issue of multilingualism is rapidly gaining attention in the current climate of globalization and linguistic connection, new dimensions of it are emerging which need to be tackled and addressed theoretically as well as practically. Multilingualism also needs to be incorporated in languaging practices both inside and outside of the classroom. Blackledge and Creese (2007) are of the view that new multilingualisms are emerging, because students create meaning with reference to their "diverse linguistic repertoires". Multilingualism is a process through which learners construct, challenge, and evaluate their world views. It is need of the hour to understand the social and cultural dynamism of multilingualism and this book represents a significant advance in this regard. The edited volume includes nineteen chapters schematically divided into four parts, namely: Towards a Multilingual Paradigm in Foreign Language Education (part one), Languaging Practices in Multilingual Classrooms (part two), Teacher and Learner Perspective (part three), and Innovative Multilingual Pedagogies in Foreign Language Classrooms (part four). Part one, which contains three chapters, explains the shift towards the multilingual paradigm in foreign language education and highlights the importance of teacher's knowledge and multilingual preparedness, responsive teaching and learning, and intercultural awareness in a multilingual context. Part two delineates languaging practices in multilingual classrooms with special reference to English language teaching [ELT]. It also enumerates various means used to integrate multilingualism and translanguaging in the Netherlands along with Indonesian cultural perspectives. Part three sheds light on teachers' and learners' attitudinal approaches towards linguistically diverse classroom settings specifically in France, Germany and Sweden. Giving credit to linguistic, social and cultural identities to create an inclusive classroom environment is the hallmark of translanguaging. This part emphatically underlines the need for a holistic approach while meticulously enumerating languaging practices of various linguistic communities including Cyprus, the US, Norway and Japan. Part four is a robust and in-depth treatment of research reports, which highlight functioning pedagogies based on multilingual approaches in foreign language education. These approaches foster an inclusive language learning environment by granting students an opportunity for plurilingual experience and cultural immersion, which enhance the relish and delight of language learning while mitigating linguistic and cultural isolation. This part also speaks to opportunities and challenges likely to be faced by teachers while implementing pedagogical practices that emphasize multilingual inclusiveness. Hence, the book encompasses variety of areas of multilingualism, including modern research, beliefs and attitudes, practices and its likely challenges. The primary objective of the book is to help us "embrace the multilingual turn in language education." People who may benefit from this edited volume include teachers, researchers and even students who are set to achieve their desired language learning targets in multilingual scenarios. Owing to its in-depth discussion and profound analytical approach, the book thoroughly outlines language teaching and learning practices which may be helpful in the modern global multilingual context, including the modern concept of pedagogical translanguaging. Teachers as well as students can embrace the strategies stated in different chapters and use the book to maximize their learning experience. The book is inspiring for teachers who want to keep themselves abreast of the paradigm shift in foreign language teaching in multilingual classrooms and desire to take advantage of learners' linguistic repertoires. Upholding the value of multilingual approaches, Chapter 1 delineates the dynamics of the paradigm shift in language teaching in multilingual scenarios. Language education can be revamped by implementing linguistically responsive approaches. In Chapter 2, the writer underlines the need to open up language teaching spaces including EFL classrooms for implementation of multilingualism. The chapter calls for a holistic approach towards teaching and learning along with the reorientation of institutional policies with multilingualism. Chapter 3 presents an interpretive framework for using picture books to promote intercultural awareness. Although the framework is specific to the Vietnamese cultural context, the basic premise behind this is that multicultural texts can be instrumental in enhancing learners' intercultural understanding. Moreover, the teacher who is well equipped with cultural knowledge is in a better position to help learners relate symbols of other cultures to their own. The thematic focus of part 2 is languaging practices in multilingual classrooms. Chapters in this section demonstrate how previously learned languages can be helpful in learning new languages and how learners and teachers can draw upon learners' resources in the pursuit of linguistic competence. In this regard, Chapter 4 cautions against limitations of monolingual approaches in multilingual classrooms while underlining the importance of proper teacher training and the provision of adequate teaching resources. Chapter 5 presents multilingual activities that were developed for a multilingual secondary education project in the Netherlands.